2021
DOI: 10.3390/su13020663
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Fishing and Aquaculture Activities in the Atlantic Coast of the Portuguese North Region: Multi-Stakeholder Views as a Tool for Maritime Spatial Planning

Abstract: The experienced view of stakeholders is a very valuable tool to build inclusive and reliable maritime spatial planning (MSP). Within this context, the present work assesses the potential and limitations for a further sustainable development of fishing and aquaculture activities, considering the Portuguese North Region as case study. The official strategies and legal framework drafted by Portugal in MSP issues were initially reviewed, with the corresponding management objectives identified. Official statistical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…It is also interesting to highlight the high relevance assigned to the sustainability of environmental resources, adequately identifying potential negative impacts such as water pollution, climate change, and marine litter. These results agree with perceptions recently expressed in a multi-stakeholder survey also conducted in the Portuguese north-western region, in which the fishery stakeholders showed a similar discrepancy with regards to the government management, as well as the existing legal framework and the planning tools, but were aware of major environmental issues [13]. The involvement of stakeholders must constitute a key element in ecosystembased MSP [41,42], and European projects have actively promoted their participation in relevant geopolitical areas (source: European Commission, Maritime Affairs, Integrated Maritime Policy, https://ec.europa.eu/, accessed on 16 November 2021).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…It is also interesting to highlight the high relevance assigned to the sustainability of environmental resources, adequately identifying potential negative impacts such as water pollution, climate change, and marine litter. These results agree with perceptions recently expressed in a multi-stakeholder survey also conducted in the Portuguese north-western region, in which the fishery stakeholders showed a similar discrepancy with regards to the government management, as well as the existing legal framework and the planning tools, but were aware of major environmental issues [13]. The involvement of stakeholders must constitute a key element in ecosystembased MSP [41,42], and European projects have actively promoted their participation in relevant geopolitical areas (source: European Commission, Maritime Affairs, Integrated Maritime Policy, https://ec.europa.eu/, accessed on 16 November 2021).…”
Section: Discussionsupporting
confidence: 90%
“…The approval and implementation of the Maritime Spatial Plan for continental Portugal [14] has legally established a new action framework for the fishing industry. Even though the involved players have recently stated that, nowadays, the conflicts between maritime activities are practically nonexistent in the Portuguese NW region, they predicted that conflicts will arise when new maritime activities intend to use maritime space currently occupied exclusively by fisheries [13]. This perception is supported by the recent conflict that arose from the installation of an offshore wind power plant in Viana do Castelo (WindFloat Atlantic project, source: EDP, Energias de Portugal, S.A., https://www.edp.pt, accessed on 16 November 2021), revealing how extremely sensitive the regional SSF is to new initiatives of maritime exploration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If combined with an anchor failure as well, the whole aquaculture system becomes unfit for the sea. All studied areas had significant wave heights that exceeded 6 m. According to [119], until further technological solutions allow offshore aquaculture to be developed, the coastal modality is a more pragmatic option for the North Region (Area A) in Portugal. Area E comes close to the wave height studied by [148] with a significant height of 6.97 m. In this area, if the anchor system does not fail, the aquaculture production system should endure storm conditions, and if the aquaculture cage can be successfully placed, other variables need to be added for the biological necessities of the selected species.…”
Section: Waves Currents and Equipmentmentioning
confidence: 99%
“…In this study, data from October 2018 and April 2019 field surveys showed, as expected, that ammonia and nitrite concentrations are well below the toxic limit for any selected fish species that can be farmed in these marine areas. Similarly, dissolved oxygen, salinity, and pH levels are within the optimal range for developing marine fish farming [30,[119][120][121][122][123]. In general, the data from the field surveys highlight the good quality of the water and its potential for the implementation of new productions.…”
Section: Fishmentioning
confidence: 99%